2020
DOI: 10.2196/16370
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Social Media–Based Recruitment and Perceived Acceptability of Digital Health Interventions for Caregivers of Justice-Involved Youth: Mixed Methods Study

Abstract: Background Caregiver involvement is critical for supporting positive behavioral health and legal outcomes for justice-involved youth; however, recruiting this population into clinical research studies and engaging them in treatment remain challenging. Technology-based approaches are a promising, yet understudied avenue for recruiting and intervening with caregivers of justice-involved youth. Objective This mixed methods study aimed to assess the feasibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…JJ staff also responded favorably, stating that the TBRI intervention was feasible and acceptable, and that they observed positive behavioral changes among youth who participated. Staff emphasized the value of TBRI for increasing family support and involvement during the reentry process, corroborating literature emphasizing the importance of family involvement in substance prevention [31,32]. Further, data collected as part of adaptation efforts document improvement in outcomes among eight youth that participated in theater testing.…”
Section: Discussionsupporting
confidence: 54%
“…JJ staff also responded favorably, stating that the TBRI intervention was feasible and acceptable, and that they observed positive behavioral changes among youth who participated. Staff emphasized the value of TBRI for increasing family support and involvement during the reentry process, corroborating literature emphasizing the importance of family involvement in substance prevention [31,32]. Further, data collected as part of adaptation efforts document improvement in outcomes among eight youth that participated in theater testing.…”
Section: Discussionsupporting
confidence: 54%
“…Children communicate too much in cyberspace, then knowledge about the ins and outs of communicating in real life, such as body language and tone of voice, becomes reduced. This condition will indirectly cause delinquency in adolescents (10,19). At the level in the family, parental behavioral control negatively predicts juvenile delinquency.…”
Section: Juvenile Delinquency(y)= -1994 + 130*(parental Marital Disco...mentioning
confidence: 99%
“…Social media platforms also have potential for engaging family/CSOs. A recent study that surveyed caregivers of justice-involved youth found high rates of social media use and interest in social media-based parenting support ( Folk et al, 2020 ).…”
Section: Putting Telehealth To Work: Provider-delivered and Direct-to...mentioning
confidence: 99%